The eye of the tongue sole Cynoglossus bilineatus (Lacepède, 1802) (Teleostei: Pleuronectiformes). (February 2022) - Nag, T.C.; Chakraborti, S.; Das, D.
Highlights: Intraretinal vessels are present in Cynoglossus bilineatus . The retina shows a lipidic tapetum lucidum in retinal pigment epithelium. The optic disc shows cytokeratin positive elongated astrocytes. The choroid possesses 3-4 rows of iridophores with stacks of cytoplasmic platelets. The sclera is fibrous (collagenous). Abstract: We report the ocular features of the tongue sole, Cynoglossus bilineatus (Lacepède, 1802), a marine, bottom-dwelling flatfish. In this species, both eyes are located juxtaposed on the same side of the flat head. Histology revealed the sclera to be fibrous (collagenous) in nature. The choroid possesses the choriocapillaris, and adjacent to it, 3–4 rows of iridophores with stacks of cytoplasmic platelets. No choroidal gland is present. The retinal pigment epithelium (RPE) contains scanty melanin granules. Its vitread half is modified into a dense tapetum with lipid spheres (about 0.34 μm in diameter). In juveniles, the tapetal spheres arise by budding from the smooth endoplasmic reticulum of the RPE. There are blood vessels within the retina; the vitreal vessels penetrate the retina and ramify close to the level of the outer limiting membrane. The vessels are capillaries in nature. The photoreceptor layer contains abundant rods, and twin cones and single cones, being arranged into square mosaics. The optic disc is non-pleated and shows pan- cytokeratin immunopositivity, which is related to the bundled cytokeratin filaments detected in astrocytes by electron microscopy. The retinal tapetum and choroidal iridophores help the species to live in a muddy bottom having dim-light environment. The lack of a choroidal gland, hypoxic aquatic condition and presence of a dense retinal tapetum (that limits O2 transport to the photoreceptors) appear to have favored the proliferation of vitreal vessels within the retina in this species. The fibrous sclera has probably arisen to provide structural support to the eye in migration from the lateral to the dorsal aspect of the head during larval metamorphosis.